Does dissolved organic carbon regulate biological methane oxidation in semiarid soils?. (23rd April 2013) - Sullivan, Benjamin W.; Selmants, Paul C.; Hart, Stephen C.
Abstract In humid ecosystems, the rate of methane (CH4) oxidation by soil‐dwelling methane‐oxidizing bacteria (MOB) is controlled by soil texture and soil water holding capacity, both of which limit the diffusion of atmospheric CH4 into the soil. However, it remains unclear whether these same mechanisms control CH4 oxidation in more arid soils. This study was designed to measure the proximate controls of potential CH4 oxidation in semiarid soils during different seasons. Using a unique and well‐constrained 3‐million‐year‐old semiarid substrate age gradient, we were able to hold state factors constant while exploring the relationship between seasonal potential CH4 oxidation rates and soil texture, soil water holding capacity, and dissolved organic carbon (DOC). We measured unexpectedly higher rates of potential CH4 oxidation in the wet season than the dry season. Although other studies have attributed low CH4 oxidation rates in dry soils to desiccation of MOB, we present several lines of evidence that this may be inaccurate. We found that soil DOC concentration explained CH4 oxidation rates better than soil physical factors that regulate the diffusion of CH4 from the atmosphere into the soil. We show evidence that MOB facultatively incorporated isotopically labeled glucose into their cells, and MOB utilized glucose in a pattern among our study sites that was similar to wet‐season CH4 oxidation rates. This evidence suggests that DOC, which is utilized by MOB in other environments with varying effects on CH4 oxidation rates, may be an important regulator of CH4 oxidation rates in semiarid soils. Our collective understanding of the facultative use of DOC by MOB is still in its infancy, but our results suggest it may be an important factor controlling CH4 oxidation in soils from dry ecosystems.